Changes In the Intensity of Urban Traffic Based on the Occupancy Of P&R Car Parks: A Research in Krakow, Poland - MONIKA BOROWIEC-GABRYŚ; SŁAWOMIR DOROCKI (Communications of International Proceedings, 2025)
The policy of the European Union focuses on rationalizing the individual use of cars and improving the quality of urban public transport. Shaping the transport system in urbanized areas requires exerting various kinds of impact on the mobility of the resi-dents. In order to improve transport accessibility and help integrate innovative car park management solutions, Sustainable Urban Mobility Plans are being introduced. They are aimed at improving the mobility and quality of life of residents and tourists. The subject of the analyses undertaken were all P&R car parks operating in a closed system in Krakow. The aim of the research was to determine the importance of P&R in urban transport policy, the principles of this system's functioning and trends in daily, weekly and monthly occupancy in 2022-2024. P&R facilities are very important with regard to enabling the so-called Clean Transportation Zones to function. The analysis was based on extensive unpublished statistical data from “vehicle history reports” obtained from the former company Municipal Infrastructure LLC (Miejska Infrastruktura Sp. z o.o.) and the Public Transport Authority in Krakow. The analysis used a varie-ty of basic statistical methods using SAS OnDemand for Academics and Statistica 13.3 software. The increasing interest taken in P&R was reduced due to the Covid 19 pandemic, but presently there appears a renewed increase in car park occupancy. The occupancy rate depends on the location of car parks. There is a very high demand for further investments of this type. At all P&R facilities, one can observe rhythmicity resulting from the holiday period and the function of Krakow as an academic centre, as well as rhythmicity in the circadian rhythm and weekly rhythm.
Keywords: sustainable transport; parking P&R; urban transport; Sustainable Urban Mobility Plans; urban mobility